Analisis Faktor yang berhubungan dengan Kejadian Karies Gigi pada Anak di SDN 44 Palembang - Rizcita Prilia Melvani (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Dental caries is a disease which leads to cavities. Based on the Health Profile of Palembang in Puskesmas Dempo, from 2,542 students who were tested there were 1,697 of students needed dental care and oral. Based on information from the Poli Dental Health Center Dempo in Palembang, it revealed that many students in SDN 44 Palembang suffered dental caries. The aim of this study was to know the relationships between dental and oral personal hygiene and lifestyle toward dental caries of students in SDN 44 Palembang, which was conducted from October to November 2019. This study used quantitative research methods with cross sectional approach. The population of this study was all students grades 4-6 in SDN 44 Palembang. The total of population was 242 students and 71 students were selected as sample using accidental sampling method. The research instrument used in the form of questionnaires and medical equipment dental and oral examination. The results showed that there was a relationship between the teeth and mouth personal hygiene including social practice (p value 0.004) and knowledge (p value 0.01) and the incidence of dental caries, while socioeconomic (p value 0.464) had no relationship to the incidence of dental caries. In addition, there was a relationship between lifestyle associated with dental and oral including health behaviours (p value 0.022) and consumption of food and beverages cariogenic (p value = 0.02), whereas the consumption of empek-empek vinegar (p value 0.639) did not have a relationship with the incidence of caries tooth.